The psychology of totalitarianism - Desmet, Mattias (White River Junction, Vermont : Chelsea Green Publishing, 2022)
"Occasionally, there are books that try to make sense of a key moment in history - and become an indispensable guide to the times we live in. This book is one of them. In The Psychology of Totalitarianism, world-renowned Professor of Clinical Psychology Mattias Desmet deconstructs the societal conditions that allow collective psychosis to take hold. By analysing our current global situation and identifying the phenomenon of 'mass formation' - a type of collective hypnosis - he illustrates how close we are to repeating totalitarian behaviours within democratic structures. Totalitarianism is not a coincidence and does not form in a vacuum. Desmet explains how it arises from a collective psychosis that has followed a predictable script throughout history, its formation gaining strength and speed with each generation - from the Jacobins to the Nazis and Stalinists - in lockstep with technological advances. He demonstrates how governments, mass media and other large, 'mechanised' forces use fear, loneliness and isolation to demoralise populations to exert control, persuading large groups of people to act against their own interests, always with destructive results. Building on Hannah Arendt's essential work on totalitarianism, The Origins of Totalitarianism, Desmet offers a sharp critique of the cultural 'groupthink' that existed pre-pandemic but has steadily and inexorably advanced during the Covid crisis. He cautions against the dangers of our current societal landscape, media consumption and reliance on manipulative technologies and then offers simple solutions - both individual and collective - to prevent the willing sacrifice of our freedoms. The Psychology of Totalitarianism describes exactly how, during this extraordinary time of loneliness, free-floating anxiety and fear, we are surrendering our freedoms and giving way to censorship and loss of privacy - driven by a dominant crisis narrative that excludes dissident views and relies on destructive groupthink"--
"The world is in the grips of mass formation-a dangerous, collective type of hypnosis-as we bear witness to loneliness, free-floating anxiety, and fear giving way to censorship, loss of privacy, and surrendered freedoms. It is all spurred by a singular, focused crisis narrative that forbids dissident views and relies on destructive groupthink. Desmet's work on mass formation theory was brought to the world's attention on The Joe Rogan Experience and in major alternative news outlets around the globe. Read this book to get beyond the sound bites! Totalitarianism is not a coincidence and does not form in a vacuum. It arises from a collective psychosis that has followed a predictable script throughout history, its formation gaining strength and speed with each generation-from the Jacobins to the Nazis and Stalinists-as technology advances. Governments, mass media, and other mechanized forces use fear, loneliness, and isolation to demoralize populations and exert control, persuading large groups of people to act against their own interests, always with destructive results. In The Psychology of Totalitarianism, world-renowned Professor of Clinical Psychology Mattias Desmet deconstructs the societal conditions that allow this collective psychosis to take hold. By looking at our current situation and identifying the phenomenon of "mass formation"-a type of collective hypnosis-he clearly illustrates how close we are to surrendering to totalitarian regimes. With detailed analyses, examples, and results from years of research, Desmet lays out the steps that lead toward mass formation, including: An overall sense of loneliness and lack of social connections and bonds A lack of meaning-unsatisfying "bullsh*t jobs" that don't offer purpose Free-floating anxiety and discontent that arise from loneliness and lack of meaning Manifestation of frustration and aggression from anxiety Emergence of a consistent narrative from government officials, mass media, etc., that exploits and channels frustration and anxiety In addition to clear psychological analysis-and building on Hannah Arendt's essential work on totalitarianism, The Origins of Totalitarianism-Desmet offers a sharp critique of the cultural "groupthink" that existed prior to the pandemic and advanced during the COVID crisis. He cautions against the dangers of our current societal landscape, media consumption, and reliance on manipulative technologies and then offers simple solutions-both individual and collective-to prevent the willing sacrifice of our freedoms. "We can honor the right to freedom of expression and the right to self-determination without feeling threatened by each other," Desmet writes. "But there is a point where we must stop losing ourselves in the crowd to experience meaning and connection. That is the point where the winter of totalitarianism gives way to a spring of life." "Desmet has an . . . important take on everything that's happening in the world right now."-Aubrey Marcus, podcast host "[Desmet] is waking a lot of people up to the dangerous place we are now with a brilliant distillation of how we ended up here."-Robert F. Kennedy, Jr"--
Originally published in Belgium by Pelckmans Publishers in 2022 as De Psychologie van Totalitarisme.
Includes bibliographical references and index.
110756
Keywords: Totalitarianism -- Psychological aspects; Social psychology -- Political aspects; Political Ideologies -- Facism and totalitarianism; Civil Rights